2022
DOI: 10.3390/v14102224
|View full text |Cite
|
Sign up to set email alerts
|

Molnupiravir When Used Alone Seems to Be Safe and Effective as Outpatient COVID-19 Therapy for Hemodialyzed Patients and Kidney Transplant Recipients

Abstract: Background: Molnupiravir demonstrated an in vitro antiviral activity against positive-sense RNA viruses, including SARS-CoV-2. The study aimed to present the results of outpatient molnupiravir use in kidney transplant recipients and hemodialysis patients during the first months of 2022 in Poland. Methods: The retrospective observational cohort study at one kidney transplant center included 36 patients diagnosed with COVID-19 with an automated nucleic acid amplification test on nasopharyngeal swab specimens. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…However, most existing studies have focused on the immunogenicity of booster vaccination, and its real-world benefits on the clinical outcomes of COVID-19 have less been investigated in the HD population, particularly in those receiving oral antiviral agents. In addition, although the combination of SARS-CoV-2 vaccines and antiviral treatments is considered beneficial for patients with COVID-19 who are at high risk of disease progression, current reports have yielded mixed results on this issue, and the integrated effects of vaccination and oral antiviral agents have yet to be characterized in HD patients [ 34 , 35 , 49 , 50 ]. A previous study utilizing an agent-based mathematical model suggested that combining SARS-CoV-2 vaccines and antiviral treatments could synergistically reduce COVID-19-related hospitalization and mortality in the overall population [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most existing studies have focused on the immunogenicity of booster vaccination, and its real-world benefits on the clinical outcomes of COVID-19 have less been investigated in the HD population, particularly in those receiving oral antiviral agents. In addition, although the combination of SARS-CoV-2 vaccines and antiviral treatments is considered beneficial for patients with COVID-19 who are at high risk of disease progression, current reports have yielded mixed results on this issue, and the integrated effects of vaccination and oral antiviral agents have yet to be characterized in HD patients [ 34 , 35 , 49 , 50 ]. A previous study utilizing an agent-based mathematical model suggested that combining SARS-CoV-2 vaccines and antiviral treatments could synergistically reduce COVID-19-related hospitalization and mortality in the overall population [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study utilizing an agent-based mathematical model suggested that combining SARS-CoV-2 vaccines and antiviral treatments could synergistically reduce COVID-19-related hospitalization and mortality in the overall population [ 49 ]. Two observational studies in Poland and Japan suggested that combining booster vaccination and molnupiravir treatment was associated with a shorter illness duration and fewer medical requirements in HD patients with COVID-19, although the sample sizes were both small [ 34 , 35 ]. In contrast, another open-label trial addressing the effects of molnupiravir in a highly vaccinated population in the UK (3-dose vaccination, 94%) indicated that hospitalization and mortality might be primarily avoided via extensive vaccination rather than antiviral agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies which investigated the efficacy of molnupiravir in the context of the dialysis population. Poznansk and colleagues presented a retrospective cohort study reporting on the use of molnupiravir in 20 dialysis patients with positive COVID-19 test results [ 99 ]. These patients received a regimen of 800 mg of molnupiravir twice daily for 5 days.…”
Section: Treatment Strategies For Elderly Haemodialysis Patients Infe...mentioning
confidence: 99%
“…None of the patients suffered adverse effects attributed to molnupiravir‚ and no adjustment of tacrolimus dose was needed 56 . Another retrospective cohort study of 16 kidney transplant patients showed that molnupiravir resulted in improvement of clinical symptoms and no serious side effects were reported, but then, this was not compared to any control 57 . Therefore, given the NIH recommendation as well as the lack of data to support its use in the transplant population, molnupiravir should be used only when the first-line options of remdesivir or nirmatrelvir-ritonavir are not available.…”
Section: Introductionmentioning
confidence: 99%